Reciclaje y homenaje en la ciudad televisiva de La antena (Esteban Sapir, 2007) - Amanda Holmes (Nuevo mundo - Mundos Nuevos, 2012)
This article interprets the representation of the city in the Argentine film, The Aerial (2007) directed by Esteban Sapir. I argue that through the intertextual, surrealist and, at times, ludic relationship that this film maintains with works from cinema’s silent era, especially Fritz Lang’s Metropolis (1926), The Aerial criticizes the oppressive control imposed by contemporary multimedia companies and demands a resistance of this power that is represented as totalitarian. Since the 1990s, the globalized economy has led to the deregularization and the privatization of the media in Argentina. Under these conditions, possibilities for communication have diminished even though the number of television programs has expanded. While the recycling of images and classical techniques from the first eras of cinema serves to underscore the artificiality of the filmic, Sapir’s second feature length film critiques the omnipresence of the media in contemporary Latin America.